2015
DOI: 10.1007/s10597-014-9807-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Home Visit Intervention on Re-hospitalization Rates in Psychiatric Patients

Abstract: To examine the home visit intervention (HoVI) effects on the re-hospitalization rate and medical costs in patients with schizophrenia or other psychiatric disorders. The subjects who received more than 3 HoVIs were defined as the HoVI group, whereas the subjects who received equal to or less than 3 HoVIs were defined as the HoVI < 4 group; the subjects who had never received an HoVI were defined as the non-HoVI group. Differences in the re-hospitalization rates and National Health Insurance (NHI) costs among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
0
14
0
3
Order By: Relevance
“…The leisure activities in the home‐care group depended on the families or self‐arrangement. In addition, many previous studies have shown that home care can help with multiple life functions and can help patients with severe mental illness to live independently in the community …”
Section: Discussionmentioning
confidence: 99%
“…The leisure activities in the home‐care group depended on the families or self‐arrangement. In addition, many previous studies have shown that home care can help with multiple life functions and can help patients with severe mental illness to live independently in the community …”
Section: Discussionmentioning
confidence: 99%
“…17 In the findings of this study, the professors use home visiting to access the population as this is an important way to reduce the search for specialized services, as well as to reduce mental health hospitalization rates. 18 The extension activities in mental health proposed by the public HEIs has been a choice of professors for teaching mental health in PHC, and offers the student the opportunity to develop in articulation with the social reality. The Mental Health Academic Leagues stand out for taking health promotion actions in the community, as well as recovery, maintenance and rehabilitation actions, in addition to promoting in the student the scientific reasoning and critical thinking that add values and differential in their formation.…”
Section: /13mentioning
confidence: 99%
“…Home visits can reduce re-hospitalization rate from 42.1% to 11.6% (Chang & Chou, 2015). Hospital stay duration and medical costs are also significantly decreased (Chang & Chou, 2015;Sharifi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Home visits can reduce re-hospitalization rate from 42.1% to 11.6% (Chang & Chou, 2015). Hospital stay duration and medical costs are also significantly decreased (Chang & Chou, 2015;Sharifi et al, 2012). However, it is not easy for patients with severe mental health problems to return to the community successfully; over 75% of such patients found it was difficult to reach this goal (Miyamoto, Hashimoto-Koichi, Akiyama, & Takamura, 2015).…”
Section: Introductionmentioning
confidence: 99%